2019
DOI: 10.1136/flgastro-2019-101237
|View full text |Cite
|
Sign up to set email alerts
|

Early real-world effectiveness of ustekinumab for Crohn’s disease

Abstract: ObjectiveTo understand the effectiveness of ustekinumab in treating Crohn’s disease (CD) in a UK real-world setting.DesignRetrospective cohort study using prospectively maintained clinical records.SettingSingle UK inflammatory bowel disease centre.PatientsAdult patients with an established diagnosis of CD prescribed ustekinumab outside of clinical trials at University Hospital Southampton (UHS).InterventionsUstekinumab, a monoclonal antibody to the shared p40 subunit of interleukin (IL) 12 and IL-23 as part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 20 publications
4
43
1
1
Order By: Relevance
“…Other above-mentioned studies also included patients with a mild disease at baseline, for example, the work by Alric et al (median HBI = 6) or by Biemans et al (HBI = 7), but the percentage of patients on steroids was lower compared to our cohort (28% and 15.8%, respectively). 11,12 Concerning treatment persistence, our patients showed a very high persistence, with 89% at 52 weeks, but similar high rates when reported were achieved with 83.6%, 17 80%, 15 and 71.5%. 12 In all the aforementioned studies, including the present one, an 8-week interval regimen was followed in the majority of patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Other above-mentioned studies also included patients with a mild disease at baseline, for example, the work by Alric et al (median HBI = 6) or by Biemans et al (HBI = 7), but the percentage of patients on steroids was lower compared to our cohort (28% and 15.8%, respectively). 11,12 Concerning treatment persistence, our patients showed a very high persistence, with 89% at 52 weeks, but similar high rates when reported were achieved with 83.6%, 17 80%, 15 and 71.5%. 12 In all the aforementioned studies, including the present one, an 8-week interval regimen was followed in the majority of patients.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, 15 patients discontinued treatment mainly because of primary or secondary failure, and only 2 patients, excluding temporary stopping due to surgery, terminated treatment because of AEs. Similarly, in previous studies, the overall discontinuation rate was very low 11‐15 …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…UST is effective for treatment of Crohn's disease (CD) and ulcerative colitis 1‐4 . In addition to randomised controlled trials, multiple real‐world studies corroborated the effectiveness of UST in the treatment of CD 5‐19 . However, the risk of primary and secondary loss of response to UST has not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the patients have typically experienced several drug switches due to primary or secondary loss of response or intolerance [2]. While ustekinumab real-world studies have shown clinical benefit even in treatment-refractory CD patient cohorts, data on dosing patterns and dose optimization remain limited [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%